2000
DOI: 10.1073/pnas.090099497
|View full text |Cite
|
Sign up to set email alerts
|

Inverse radiation dose-rate effects on somatic and germ-line mutations and DNA damage rates

Abstract: The mutagenic effect of low linear energy transfer ionizing radiation is reduced for a given dose as the dose rate (DR) is reduced to a low level, a phenomenon known as the direct DR effect. Our reanalysis of published data shows that for both somatic and germ-line mutations there is an opposite, inverse DR effect, with reduction from low to very low DR, the overall dependence of induced mutations being parabolically related to DR, with a minimum in the range of 0.1 to 1.0 cGy͞min (rule 1). This general patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(69 citation statements)
references
References 72 publications
(71 reference statements)
2
64
1
2
Order By: Relevance
“…Data from the irradiation of spermatogonia in mice have been published by two groups led, respectively, by Lyon (3) and Russell (4,5). From their published results we have calculated the DREs and shown that their sets of data are in close agreement (1). Both show a direct DRE at DRs above 1.0 cSv͞min; i.e., the frequency of mutations increases as the rate of delivery of a given dose increases.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…Data from the irradiation of spermatogonia in mice have been published by two groups led, respectively, by Lyon (3) and Russell (4,5). From their published results we have calculated the DREs and shown that their sets of data are in close agreement (1). Both show a direct DRE at DRs above 1.0 cSv͞min; i.e., the frequency of mutations increases as the rate of delivery of a given dose increases.…”
Section: Resultsmentioning
confidence: 73%
“…We previously concluded that cells are able to measure the frequency of DNA damage and to compare that frequency with a ''spontaneous,'' or background, frequency (1). The mechanism would therefore resemble that of ''stochastic resonance'' that is observed for signal-to-noise relationships in physics and physiology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in humans, the primary DSB repair pathway is somewhat errorprone, and therefore, the fidelity of the genome is not always maintained (2)(3)(4)(5). This may be particularly important following the production of low levels of DNA damage in which cellular detection mechanisms may not be fully elicited (5,6). Evidence exists (7) that increased cell death in the absence of repair following low level DNA damage may offer a way by which the cell prevents potentially promutagenic lesions from being passed on to progeny.…”
mentioning
confidence: 99%